2004
DOI: 10.1002/food.200300429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ‐irradiation on aflatoxin B1 production by Aspergillus flavus and chemical composition of three crop seeds

Abstract: The effect of gamma-irradiation on aflatoxin B1 production by Aspergillus flavus, and the chemical composition of some different crop seeds were investigated. A. flavus infected seeds behaved differently according to their principal constituents. A. flavus caused an increase in protein and decrease in lipids and carbohydrate contents of wheat, soyabean and fababean seeds. Growth of A. flavus and production of aflatoxin B1 was inhibited at a dose level of 5 kGy. A. flavus utilizes carbohydrates of seeds for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Thus, the rising of AFB1 could be attributed to the constant growth and metabolism of the remaining Aspergillus flavus , which did not killed by γ‐irradiation and produced some toxin. There had some studies showed that AFB1 production decreased with the increasing level of irradiation and that doses of 4–6 kGy were effective for the reduction of AFB1 (Aziz & Mahrous, ; Aziz et al, ; Iqbal et al, ). Therefore, it could be concluded that irradiation effectively restrained the increase in mycotoxins by reducing the fungal load (Iqbal et al, ), not the degradation on mycotoxins.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the rising of AFB1 could be attributed to the constant growth and metabolism of the remaining Aspergillus flavus , which did not killed by γ‐irradiation and produced some toxin. There had some studies showed that AFB1 production decreased with the increasing level of irradiation and that doses of 4–6 kGy were effective for the reduction of AFB1 (Aziz & Mahrous, ; Aziz et al, ; Iqbal et al, ). Therefore, it could be concluded that irradiation effectively restrained the increase in mycotoxins by reducing the fungal load (Iqbal et al, ), not the degradation on mycotoxins.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that there would be no remaining mycotoxins in food commodities irradiated with dose up to 10-20 kGy. Hence food treated in this way should no longer require testing for presence of mycotoxins, provided there is no opportunity for subsequent contamination and growth of moulds after application of the irradiation treatment (Aziz & Mahrous, 2004;Aziz, Mahrous, & Youssef, 2002;Mahrous, Youssef, & Aziz, 2000;Seda, Mahmoud, Ibrahim, & El-Niely, 2002).…”
Section: Distribution Of Fusarium Moulds and Fumonisin B 1 In Diverenmentioning
confidence: 96%
“…Various methods of preservation have been applied to arrest growth of moulds in foods such as fumigation and heat treatment, but none of these methods oVers complete control of toxigenic moulds. Ionizing radiation is one of the methods applied to decontaminate pathogenic microorganisms in diVerent food commodities (Aziz & Mahrous, 2004;Aziz & Moussa, 2002Mahrous, Aziz, & Shahin, 2003;Refai, Niazi, Aziz, & Khafaga, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are not significantly affected during irradiation at less than 10 kGy (Aziz and Mahrous ). In contrast to other preservation methods (such as pasteurization), protein denaturation is also not significant (Lado and Yousef ).…”
Section: The Food Irradiation Technologymentioning
confidence: 99%